The Pineal Hypothesis for Drug Dependence - Francesco, Crespi (International Physiology Journal, 2018)
The pineal gland constitutes a major neuroendocrine organ in the brain. By mean of its neurohormone melatonin it transduces exogenous signals such as circadian and seasonal variations of light and temperature into proper hormonal changes which adjust and adapt internal endocrine functions. Alteration of circadian rhythms has been associated with affective disorders, psychosomatic diseases and cancer. It has been observed that light deprivation, which stimulates (the enzymes responsible for) melatonin production in the pineal, enhances the animal's ethanol preference. Similarly, administration of the pineal hormone to rats maintained under normal conditions of constant photoperiod also induced ethanol drinking. Our hypothesis is that in normal conditions melatonin might be acting as a cerebral "pacemaker", sensitive to endogenous as well as exogenous stimuli in the attempt to maintain an equilibrate circadian interaction between the cerebral activities of endogenous aminergic and opiates systems. Abnormal states (i.e. drug abuse) could result in altered pineal activity, then in rhythmically altered functions of cerebral opiates and/or monoamine neurotransmitters. This may led to the development of a “reward - urge for drug rhythm” resulting in craving, ending in addiction.
Keywords: neurohormone; affective disorders; psychosomatic diseases and cancer